The Effect of Marine Fish Biomass Stock Reduction to Fishers Revenue (A Case Study of Sardinella Lemuru Fisheries on Bali Strait) - Ratna Purwaningsih; Sjarief Widjaja; Sri Gunani Partiwi (IPTEK The Journal for Technology and Science, 2011)
Stock assessment studies indicate that Sardinela Lemuru fisheries of Bali strait have been overfishing. This research attempts to (1) Identify the effect of biomass stock reduction to fishers revenue per trip, (2) Analyze the economic feasibility study for purse seine of Muncar, Banyuwangi. System Dynamic approach is used for simulation modeling. Simulation output shows a strong correlation between fish stock reduction and fisher revenue. The growth of fishing effort per year results on the reduction of catch per unit effort and total catch per year. Feasibility study concludes that purse seine (30 GT) which operates 120 trips per year is no longer a profitable business since 2020.